Characterization of outer membrane vesicles from Acinetobacter haemolyticus and their role in the dissemination of carbapenem resistance - Elsy Martínez-Gorgonio; Rosa del Carmen Rocha-Gracia; Miguel Castañeda-Lucio; Margarita M. P. Arenas-Hernández; Miguel A. Cevallos; Yolanda Sáenz; Patricia Lozano-Zarain (Medical Microbiology and Immunology, 2026)
Species outside the Acinetobacter calcoaceticus–baumannii (Acb) complex have recently emerged as new clinically relevant carbapenem-resistant pathogens, such as A. haemolyticus . A new mechanism that could contribute to the dissemination of this resistance is the secretion of outer membrane vesicles (OMVs). We investigate OMVs secreted by A. haemolyticus AN54, a Mexican clinical strain carrying a plasmid-borne bla NDM−1 gene and by its plasmid-cured derivative AN54Δe. Active secretion of OMVs formed by a lipid membrane, measuring 10–50 nm in both strains, was observed by TEM. The OMVs from AN54 possess hydrolytic capacity against carbapenem. The OMV protein profile varied depending on the antibiotic concentration during induction, with additional protein bands detected at 8 and 32 µg/ml of antibiotic exposure. Mass spectrometry identified proteins involved in different metabolic pathways and in resistance-related processes. The porins, efflux pumps, and ADC enzyme were more abundant in the OMVs from AN54Δe than in those from AN54 harboring the active NDM-1 enzyme. The OMVs protected the sensitive strains from the same and different genera against the antibiotic action for a limited period. However, the OMVs transferred the bla NDM−1 -carrying plasmid (pAhaeAN54e) only to the AN54Δe strain, conferring permanent resistance to carbapenems. Together, these findings suggest that OMVs can help protect surrounding bacteria from antibiotic action and serve as vehicles for disseminating resistance genes. These results show the importance of studying OMVs as a novel mechanism for the dissemination of antimicrobial resistance.

Network topology and structural connectivity of coral reef ecosystem in the Mexican tropical Pacific - Ubaldo Jarquín-Martínez; Andrés López-Pérez; Luis G. Abarca-Arenas; Israel Huesca-Domínguez; Ana María Torres-Huerta; Marco Ortiz; Alma P. Rodríguez-Troncoso; Amílcar Leví Cupul-Magaña; Omar Valencia-Méndez; Cristian M. Galván-Villa; Enrique Godínez-Domínguez; Seim Uriel Keller-Rodríguez; et al. (Food Webs, 2026)

Reconstructing historical patterns in bacterial communities from deep-sea sediments in the western Mediterranean: impacts of metal pollution and climatic variation - M.L. Arena-Ortíz; J.M. Ortíz-Alcántara; V. Papiol; J. Santos-Echeandía; P. Bernárdez; J.E. Cartes (Marine Environmental Research, 2026)

Interpretable machine learning of urban noise levels from street-scale morphology and functionality - Víctor Poblete; Guillermo Rey-Gozalo; Enrique Suárez; Jorge P. Arenas; Luis Veas-Castillo; Juan P. Salazar; Rafael Hayde; Luis Llanca; Diego Vergara (Sustainable Cities and Society, 2026)

Iron-rich natural mineral waste enabling the photocatalytic activation of peroxymonosulfate for the oxidation of Enterococcus faecalis and tetracycline - C. Gaye; P. García-Muñoz; J. Vazquez-Arenas; U.M. García-Pérez; J. Rodríguez-Chueca (Chemical Engineering Journal, 2026)

Supplementation with rumen-protected fats reduces rectal temperature and improves productive performance of fattening lambs under heat stress - Alma B. Jaramillo-Castro; Marco A. López-Santiago; Sandra P. Maciel-Torres; Pablo Arenas-Báez; L. Danilo Granados-Rivera; Juan González-Maldonado; Jorge A. Maldonado-Jáquez (Journal of Thermal Biology, 2026)

A case for monitoring fungi of clinical relevance at beaches: enterococci measures do not correlate with all disease risks - Larissa Montás-Bravo; Helena M. Solo-Gabriele; Débora F. Gil; Ayaaz Amirali; Sebastian P. Arenas; Sofia Hoffman; Adriana Jimenez; Alexandre Mendonça; Rivka Reiner; Raquel Sabino; Konstantina Sarioglou; Mark E. Sharkey; et al. (Environmental Monitoring and Assessment, 2026)
Fungal disease is on the rise, coupled with fungal pathogens increasing in geographic range. Studies have shown that viable fungal pathogens may be present in beach sand and water, and consequently, efforts are ongoing in Europe to develop guidelines for fungi levels at beaches. In the USA, fungal diseases are a growing concern, and yet, they are not subject to public health reporting, and beach environments are currently not routinely monitored for fungal pathogens. This study measured fungal and enterococci levels at two beaches within a subtropical environment in Miami, FL. Samples were analyzed by culture-based methods, with fungi species confirmation by targeted PCR and sequencing. A unique aspect of this study is the analysis with higher incubation temperatures (37 °C and 40 °C) to isolate mesophilic fungi that can cause invasive infections. Results show that levels of fungi were strongly influenced by sample matrix (sand or water). The most common fungal species observed belonged to the Aspergillus and Candida genera, with the isolation of 25 taxa with reports of causing infections, of which 20 were previously reported to exhibit resistance to some or all classes of antifungals available. Results emphasize the need for fungal specific analyses to better understand beach-related disease risks. Given the current increase in cases of fungal diseases and the presence of viable fungi in the environment, integrating fungal measurements in routine microbiological monitoring programs is critical for assessing the beach transmission of pathogenic fungal disease and the control of emerging fungal pathogens.

Photocatalytic disinfection of wastewater using peroxymonosulfate activated by pyrite, chalcopyrite and marcasite under solar irradiation - C. Gaye; P. García-Muñoz; J. Vazquez-Arenas; R.H. Lara; J. Rodríguez-Chueca (Chemical Engineering Journal, 2025)

Response of intertidal fucales to low-tide heat stress at their southern distributional limit - Luís F. Pereira; Cátia Monteiro; João Seródio; João Silva; Rui Seabra; Fernando P. Lima; Jorge Teixeira; Francisco Arenas (Marine Environmental Research, 2025)

Ni-based catalysts for green H2 production from valorized components of spent NiMH batteries - Karina P. de la Cruz; Issis C. Romero-Ibarra; Angel E. Yañez-Rios; Luis Lartundo-Rojas; Gabriel Trejo; Jorge Vazquez-Arenas (Journal of Environmental Chemical Engineering, 2025)

On the impact of electric vehicle transition on urban noise pollution - Jorge P. Arenas (Current Opinion in Environmental Science & Health, 2025)

Dietary vitamin D intake and 2-year changes in cognitive function in older adults with overweight or obesity and metabolic syndrome - Héctor Vázquez-Lorente; Jiaqi Ni; Indira Paz-Graniel; Estefanía Toledo; Dolores Corella; Olga Castañer; J. Alfredo Martínez; Ángel M. Alonso-Gómez; Julia Wärnberg; Jesús Vioque; Dora Romaguera; José López-Miranda; et al. (GeroScience, 2025)
The protective role of dietary vitamin D intake on cognitive function is of interest, but evidence remains inconsistent. We aimed to evaluate the association between dietary vitamin D intake and 2-year cognitive changes in older adults at risk of cognitive decline. This longitudinal study comprised 5454 individuals (aged 55–75 years in men and 60–75 years in women) who exhibited overweight/obesity and metabolic syndrome. Data on dietary vitamin D intake was assessed using a validated 143-item food frequency questionnaire. Cognitive function was assessed through five composite scores derived from a comprehensive battery of eight neuropsychological tests, encompassing global cognitive function, general cognitive function, attention, executive function, and language domains. Multivariable-adjusted linear regression models were fitted to examine the association between energy-adjusted cumulative average dietary vitamin D intake over time and 2-year changes in cognitive function. After adjusting for multiple covariates, energy-adjusted cumulative average dietary vitamin D intake as a continuous variable was associated with greater 2-year improvements in global cognitive function ( β 1.18 × 10 −2 ; 95% CI 0.19 × 10 −2 to 2.17 × 10 −2 ), executive function ( β 1.12 × 10 −2 ; 95% CI 0.03 × 10 −2 to 2.21 × 10 −2 ), and language ( β 1.61 × 10 −2 ; 95% CI 0.43 × 10 −2 to 2.78 × 10 −2 ). Additionally, the higher cumulative average dietary vitamin D intake quartile was associated with an increase in global cognitive function ( β 7.10 × 10 −2 ; 95% CI 0.59 × 10 −2 to 13.6 × 10 −2 ), language ( β 7.07 × 10 −2 ; 95% CI − 0.52 × 10 −2 to 14.7 × 10 −2 ), and a lower decline in attention ( β 9.58 × 10 −2 ; 95% CI 1.60 × 10 −2 to 17.5 × 10 −2 ). A higher dietary vitamin D intake was associated with modest favorable changes in cognitive function and a reduced cognitive decline over a 2-year period. These findings highlight the need for further research to explore the potential benefits of boosting dietary vitamin D intake for cognitive health in older adults.

Translation, cross-cultural adaptation and validation of the General Movement checklist - Daniela Eugenia Salazar-Díaz; Carlos P. Viñals-Labañino; Marcela Balderas-Campos; Elsa Alvarado-Solorio; María de la Luz Arenas-Sordo (Acta Neurologica Belgica, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Streets classification models by urban features for road traffic noise estimation - Alexandra L. Montenegro; Guillermo Rey-Gozalo; Jorge P. Arenas; Enrique Suárez (Science of The Total Environment, 2024)

Effect of a nutritional intervention based on an energy-reduced Mediterranean diet on environmental impact - Laura Álvarez-Álvarez; María Rubín-García; Facundo Vitelli-Storelli; Silvia García; Cristina Bouzas; Miguel Ángel Martínez-González; Dolores Corella; Jordi Salas-Salvadó; Mireia Malcampo; J. Alfredo Martínez; Ángel M. Alonso-Gómez; Julia Wärnberg; et al. (Science of The Total Environment, 2024)

Multimodal brain age prediction using machine learning: combining structural MRI and 5-HT2AR PET-derived features - Ruben P. Dörfel; Joan M. Arenas-Gomez; Claus Svarer; Melanie Ganz; Gitte M. Knudsen; Jonas E. Svensson; Pontus Plavén-Sigray (GeroScience, 2024)
To better assess the pathology of neurodegenerative disorders and the efficacy of neuroprotective interventions, it is necessary to develop biomarkers that can accurately capture age-related biological changes in the human brain. Brain serotonin 2A receptors (5-HT2AR) show a particularly profound age-related decline and are also reduced in neurodegenerative disorders, such as Alzheimer’s disease. This study investigates whether the decline in 5-HT2AR binding, measured in vivo using positron emission tomography (PET), can be used as a biomarker for brain aging. Specifically, we aim to (1) predict brain age using 5-HT2AR binding outcomes, (2) compare 5-HT2AR-based predictions of brain age to predictions based on gray matter (GM) volume, as determined with structural magnetic resonance imaging (MRI), and (3) investigate whether combining 5-HT2AR and GM volume data improves prediction. We used PET and MR images from 209 healthy individuals aged between 18 and 85 years (mean = 38, std = 18) and estimated 5-HT2AR binding and GM volume for 14 cortical and subcortical regions. Different machine learning algorithms were applied to predict chronological age based on 5-HT2AR binding, GM volume, and the combined measures. The mean absolute error (MAE) and a cross-validation approach were used for evaluation and model comparison. We find that both the cerebral 5-HT2AR binding (mean MAE = 6.63 years, std = 0.74 years) and GM volume (mean MAE = 6.95 years, std = 0.83 years) predict chronological age accurately. Combining the two measures improves the prediction further (mean MAE = 5.54 years, std = 0.68). In conclusion, 5-HT2AR binding measured using PET might be useful for improving the quantification of a biomarker for brain aging.

Opening and closure of Cadomian peri-Gondwanan oceans: age and evolution of the Mérida Ophiolite (SW Iberia) - R. Arenas; E. Rojo-Pérez; R. Díez Fernández; R. Albert; I. Novo-Fernández; S. Sánchez Martínez; J. M. Fuenlabrada; P. Andonaegui; D. Moreno-Martín; A. Gerdes; A. Garcia-Casco (International Geology Review, 2024)

Enhanced selectivity for acidic contaminants in drinking water: From suspect screening to toxicity prediction - Davide Ciccarelli; D. Christopher Braddock; Andrew J. Surman; Blanca Ivonne Vergara Arenas; Tara Salal; Tim Marczylo; Paolo Vineis; Leon P. Barron (Journal of Hazardous Materials, 2023)

Sleep duration and lipid metabolism in patients with diabetes mellitus: from the POWER2DM study - Isabel Perez-Corral; Francisco Gomez-Delgado; Merel M. Ruissen; Jose D. Torres-Peña; Antonio P. Arenas-de Larriva; Jacob K. Sont; Albert A. de Graaf; Bas S. Uitbeijerse; Eelco J. P. de Koning; Javier Delgado-Lista (Sleep and Biological Rhythms, 2022)

Setting Performance Indicators for Coastal Marine Protected Areas: An Expert-Based Methodology - Mariana Cardoso-Andrade; Henrique Queiroga; Mafalda Rangel; Inês Sousa; Adela Belackova; Luís Bentes; Frederico Oliveira; Pedro Monteiro; Nuno Sales Henriques; Carlos M. L. Afonso; Ana F. Silva; Bernardo R. Quintella; et al. (Frontiers in Marine Science, 2022)
Marine Protected Areas (MPAs) require effective indicators to assess their performance, in compliance with the goals of relevant national and international commitments. Achieving and prioritizing shortlists of multidisciplinary indicators demands a significant effort from specialists to depict the multiple conservation and socioeconomic interests, and the large complexity of natural systems. The present paper describes a structured expert-based methodology (process and outputs) to co-define a list of multidisciplinary MPA performance indicators. This work was promoted by the management authority of coastal MPAs in mainland Portugal to gather a consensual and feasible list of indicators that would guide the design of a future national monitoring program. Hence, Portuguese coastal MPAs served as a case study to develop such a process between 2019 and 2020. In the end, participants (1) agreed on a shortlist of prioritized indicators ( i.e. , environmental, governance, and socioeconomic indicators) and (2) defined minimum monitoring frequencies for the indicators in this list, compatible with the potential replicability of the associated survey methods. The present approach recommends that management plans incorporate monitoring procedures and survey methods, with a validated list of indicators and associated monitoring periodicity, agreed among researchers, MPA managers and governance experts. The proposed methodology, and the lessons learned from it, can support future processes aiming to define and prioritize MPA performance indicators.

A Review on Current Trends in Biogas Production from Microalgae Biomass and Microalgae Waste by Anaerobic Digestion and Co-digestion - Laura Vargas-Estrada; Adriana Longoria; Emilio Arenas; Joel Moreira; Patrick U. Okoye; Yaneth Bustos-Terrones; P. J. Sebastian (BioEnergy Research, 2022)

Correction to: Glutamine Antagonist JHU083 Normalizes Aberrant Glutamate Production and Cognitive Deficits in the EcoHIV Murine Model of HIV-Associated Neurocognitive Disorders - Michael T. Nedelcovych; Boe-Hyun Kim; Xiaolei Zhu; Lyndah E. Lovell; Arena A. Manning; Jennifer Kelschenbach; Eran Hadas; Wei Chao; Eva Prchalová; Ranjeet P. Dash; Ying Wu; Jesse Alt; et al. (Journal of Neuroimmune Pharmacology, 2021)

Glutamine Antagonist JHU083 Normalizes Aberrant Glutamate Production and Cognitive Deficits in the EcoHIV Murine Model of HIV-Associated Neurocognitive Disorders - Michael T. Nedelcovych; Boe-Hyun Kim; Xiaolei Zhu; Lyndah E. Lovell; Arena A. Manning; Jennifer Kelschenbach; Eran Hadas; Wei Chao; Eva Prchalová; Ranjeet P. Dash; Ying Wu; Jesse Alt; et al. (Journal of Neuroimmune Pharmacology, 2019)

Heavy metals in the volcanic and peri-urban terrain watershed of the River Yautepec, Mexico - Silvia Viridiana Vargas-Solano; Francisco Rodríguez-González; Martha Lucia Arenas-Ocampo; Rita Martínez-Velarde; S. B. Sujitha; M. P. Jonathan (Environmental Monitoring and Assessment, 2019)

Primary Cutaneous Mucormycosis Caused by Rhizopus oryzae: A Case Report and Review of Literature - Erika Rodríguez-Lobato; Lourdes Ramírez-Hobak; Jorge E. Aquino-Matus; Juan P. Ramírez-Hinojosa; Víctor H. Lozano-Fernández; Juan Xicohtencatl-Cortes; Rigoberto Hernández-Castro; Roberto Arenas (Mycopathologia, 2017)

Self‐fertilization, long‐distance flash invasion and biogeography shape the population structure of Pseudosuccinea columella at the worldwide scale - M. Lounnas; A. C. Correa; A. A. Vázquez; A. Dia; J. S. Escobar; A. Nicot; J. Arenas; R. Ayaqui; M. P. Dubois; T. Gimenez; A. Gutiérrez; C. González‐Ramírez; et al. (Molecular Ecology, 2017)
Population genetic studies are efficient for inferring the invasion history based on a comparison of native and invasive populations, especially when conducted at species scale. An expected outcome in invasive populations is variability loss, and this is especially true in self‐fertilizing species. We here focus on the self‐fertilizing Pseudosuccinea columella , an invasive hermaphroditic freshwater snail that has greatly expanded its geographic distribution and that acts as intermediate host of Fasciola hepatica , the causative agent of human and veterinary fasciolosis. We evaluated the distribution of genetic diversity at the largest geographic scale analysed to date in this species by surveying 80 populations collected during 16 years from 14 countries, using eight nuclear microsatellites and two mitochondrial genes. As expected, populations from North America, the putative origin area, were strongly structured by selfing and history and harboured much more genetic variability than invasive populations. We found high selfing rates (when it was possible to infer it), none‐to‐low genetic variability and strong population structure in most invasive populations. Strikingly, we found a unique genotype/haplotype in populations from eight invaded regions sampled all over the world. Moreover, snail populations resistant to infection by the parasite are genetically distinct from susceptible populations. Our results are compatible with repeated introductions in South America and flash worldwide invasion by this unique genotype/haplotype. Our study illustrates the population genetic consequences of biological invasion in a highly selfing species at very large geographic scale. We discuss how such a large‐scale flash invasion may affect the spread of fasciolosis.

Reconstructing subduction polarity through the geochemistry of mafic rocks in a Cambrian magmatic arc along the Gondwana margin (Órdenes Complex, NW Iberian Massif) - P. Andonaegui; S. Sánchez-Martínez; P. Castiñeiras; J. Abati; R. Arenas (International Journal of Earth Sciences, 2016)

The regime of climate-related disturbance and nutrient enrichment modulate macroalgal invasions in rockpools - Iacopo Bertocci; J. Domínguez Godino; C. Freitas; M. Incera; R. Araújo; A. Bio; F. Arenas; I. Sousa-Pinto; P. A. Reis; R. Domínguez (Biological Invasions, 2015)

Re-interpreting the Devonian ophiolites involved in the Variscan suture: U–Pb and Lu–Hf zircon data of the Moeche Ophiolite (Cabo Ortegal Complex, NW Iberia) - R. Arenas; S. Sánchez Martínez; A. Gerdes; R. Albert; R. Díez Fernández; P. Andonaegui (International Journal of Earth Sciences, 2014)

B25716/1: a novel albumin-binding Gd-AAZTA MRI contrast agent with improved properties in tumor imaging - E. Gianolio; C. Cabella; S. Colombo Serra; G. Valbusa; F. Arena; A. Maiocchi; L. Miragoli; F. Tedoldi; F. Uggeri; M. Visigalli; P. Bardini; S. Aime (JBIC Journal of Biological Inorganic Chemistry, 2014)

Accumulation patterns of phenolic compounds during fruit growth and ripening of Berberis buxifolia , a native Patagonian species - ME Arena; P Postemsky; NR Curvetto (New Zealand Journal of Botany, 2012)
The accumulation patterns of phenolic compounds during fruit growth and ripening of Berberis buxifolia and their correlations were studied to determine the optimal time and conditions needed to obtain maximum phenolic content. Anthocyanin content increased from 1.7 to a maximum of 752.7 mg·100 g −1 FW at the end of ripening, while the flavonoid content was maximal in unripe fruits [604.0 mg (+)‐catechin equivalents·100 g −1 FW]. Total phenolic compounds decreased from 968.1 to a minimum of 746.3 mg gallic acid equivalents·100 g −1 FW just as soluble solids started to accumulate; a maximum of 1522.9 mg gallic acid equivalents·100 g −1 FW was attained at the end of ripening. Both variables (1,1‐diphenyl‐2‐picrylhydrazyl scavenging effect and reducing power) were maximum in unripe fruits, and decreased during the ripening period, although the 1,1‐diphenyl‐2‐picrylhydrazyl scavenging effect increased again towards the end of this period. The accumulation patterns of phenols varied depending on the specific group of compounds considered, and could be correlated with fruit quality.

Life cycle assessment of construction and demolition waste management systems: a Spanish case study - Irma T. Mercante; María D. Bovea; Valeria Ibáñez-Forés; Alejandro P. Arena (The International Journal of Life Cycle Assessment, 2012)

Gas exchange and leaf metabolism of irrigated maize at different growth stages - L. Vitale; C. Arena; P. Carillo; P. Di Tommasi; B. Mesolella; F. Nacca; A. Virzo De Santo; A. Fuggi; V. Magliulo (Plant Biosystems, 2011)

Establishing physiological blood parameters in the loggerhead sea turtle (Caretta caretta) - D. Gelli; V. Ferrari; A. Zanella; P. Arena; L. Pozzi; S. Nannarelli; C. Vaccaro; D. Bernardini; S. Romagnoli (European Journal of Wildlife Research, 2009)

Role of polyamines during in vitro rhizogenesis of Nothofagus nervosa using successive culture media - G. Martínez Pastur; M. E. Arena; M. P. Benavides; E. Eliasco; N. Curvetto (New Forests, 2007)

Fish assemblages on sunken vessels and natural reefs in southeast Florida, USA - P. T. Arena; L. K. B. Jordan; R. E. Spieler (Hydrobiologia, 2007)

Effect of melatonin on hyperlipidemic nephropathy under constant light exposure - I. Túnez; M. C. Muñoz; M. Feijoo-López; E. Valdelvira; I. Bujalance-Arenas; P. Montilla (Journal of Physiology and Biochemistry, 2002)

Structural and kinematic analysis of the Corredoiras detachment: evidence for early Variscan synconvergent extension in the Ordenes Complex, NW Spain - F. Díaz García; J. R. Martínez Catalán; R. Arenas; P. González Cuadra (International Journal of Earth Sciences, 1999)